Analysis of Medication Errors in Giving Medication to Inpatients at the Pharmacy Installation at Hospital X Pekanbaru: Analysis of Medication Errors in Giving Medication to Inpatients at the Pharmacy Installation at Hospital X Pekanbaru - Amalia, Risa; Syafitri, Yenissa; Wahyudi, Arif; Alhidayati, Alhidayati (Jurnal Olahraga dan Kesehatan (ORKES), 2024)
Medication error is an error that occurs in the patient's treatment process that has the potential to harm the patient when the treatment is under the supervision of health workers which is actually preventable. The purpose of this study in general is to obtain in-depth information about medication error in the administration of inpatient drugs and the form of occurrence in the prescribing and transcribing phases. This research method uses a qualitative approach. Interviews and observations were conducted with 9 informants and 26,013 prescription sheets of inpatients who entered the Pharmacy Installation for the period of January 2022. The location of the study was conducted at the X Hospital Pekanbaru, Riau Province in February–April 2022. Based on theresearch, it was found that the incidence of the prescribing phase includes: illegible prescription writings, unclear identity of the prescription author doctor, unclear identity of the patient, unclear drug name, wrong concentration / strength of the preparation, no rules for using the drug, no date of prescription request, no allergy data, no weight, and height. In the transcribing phase include: incorrect input of the name of the drug, incorrect copying of the name of the drug, incorrect copying of the instructions of the drug. The cause of the medication error of the workload is that the ratio of workload and human resources is not balanced, while the SOP medication error adopts the reference of Permenkes No. 73 of 2016. In minimizing the occurrence of medication errors, socialization and evaluation are carried out with doctors and pharmaceutical technical personnel. From the results of the study, it can be concluded that medication errors in the hospitalization of X Hospital Pekanbaru still occur in the January 2022 period.